2018
DOI: 10.1177/0954407018762488
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies on the acoustic characteristics of the U-shaped corrugated pipes and application investigations

Abstract: This paper presents a numerical study on the effect of structural parameters on acoustical transmission loss of U-shaped corrugated pipe using the control variable method. Then, the interactions between the cutoff frequencies and structural parameters are modeled based on the dimension analysis method using the numerical results. An investigation into the application of the U-shaped corrugated pipe into a simple expansion chamber muffler is carried out using both numerical and experimental methods. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Jia et al [22] obtained the attenuation law of pipeline explosion shock waves in bifurcated pipelines. Xue et al [23,24] obtained the rule of U-shaped pipe structure on wave propagation of gas explosion. Zhu et al [25,26] found that the branching structure of pipelines can lead to turbulence by studying the flame acceleration process.…”
Section: Introductionmentioning
confidence: 99%
“…Jia et al [22] obtained the attenuation law of pipeline explosion shock waves in bifurcated pipelines. Xue et al [23,24] obtained the rule of U-shaped pipe structure on wave propagation of gas explosion. Zhu et al [25,26] found that the branching structure of pipelines can lead to turbulence by studying the flame acceleration process.…”
Section: Introductionmentioning
confidence: 99%